Zein-yeast carboxymethyl glucan particles formed by anti-solvent precipitation for encapsulating resveratrol - Bao, Xiaoying; Rong, Shuang; Fu, Qi; Liu, Hao; Han, Yahong; Liu, Fuguo; Ye, Zhan; Chen, Shuai (International journal of biological macromolecules, 2023)
In the work, zein-yeast carboxymethyl glucan (ZY) particles were fabricated by a novel ultrasonic assisted anti-solvent precipitation (ASP) method, which was a good delivery system for resveratrol. The particle size and zeta-potential of ZY samples were detected by Zetasizer Pro analyzer, they gradually increased as the mass ratio of zein and yeast carboxymethyl glucan (YCG) changed from 10:1 to 10:5. The intermolecular interactions were investigated by zeta-potentiometric analyzer, Fourier transform infrared spectroscopy and fluorescence spectroscopy. Electrostatic interaction, hydrogen bonding and hydrophobic effects between zein and YCG molecules were identified as the main driving forces in the formation of ZY particles. The optimized ZY (10:3) binary particles were used as delivery system for encapsulating and protecting resveratrol. They had high encapsulation efficiency (85.4 %) and loading capacity (6.1 %), and increased the retention rate of resveratrol by 2.10 and 1.21 folds after exposure to light and heat conditions, effectively protect resveratrol against light and thermal degradation. These particles also delayed the release of resveratrol in simulated gastrointestinal digestion, which might improve its oral bioavailability. In conclusion, ZY binary particles could be regarded as a useful and promising delivery vehicle, which might contribute to the application of hydrophobic bioactive ingredients in functional foods.